Increasing Ramadan Activities Through the Participatory Action Research - Arbonas Lubis; Umeir Ibnul Fath; Farid Ansyori; Muhammad Rasyid Riyanto; Thoriq Muhammad Kholy Lubis (ASSUNNAH PRESS, 2023)
The implementation of this research focuses on realizing that the community understands the basics of the Islamic Religion, assisting parents in educating the Muslim generation to love the Qur'an and Arabic. Then the aim is to understand the basics of Islam and foster a love for the Qur'an and Arabic in Pasa Wave Village, 2x11 Kayutanam District, Padang Pariaman Regency, West Sumatra Province. The method used is PAR (Participatory Action Research) by obtaining data through cycles to realize changes at each stage through Al-Quran recitation activities, short lectures, and religious and Arabic language learning. Finally, the activity results are significant in increasing people's interest in Religion, and their reading of the Qur'an is increasing and the emergence of a love for learning Arabic.